2004
DOI: 10.1562/0031-8655(2004)080<0416:ttinrs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Topical Isoflavonoid NV-07α Reduces Solar-simulated UV-induced Suppression of Mantoux Reactions in Humans¶

Abstract: UV radiation suppresses delayed-type hypersensitivity responses to intradermally injected tuberculin purified protein derivative in Mantoux-positive individuals. The effect of the topically administered isoflavonoid NV-07alpha, a synthetic derivative of the isoflavonoid equol, on UV-induced suppression of Mantoux reactions was assessed in 18 healthy Mantoux-positive volunteers. A single, fixed dose of solar-simulated UV radiation was delivered to the volunteers' lower backs. Different concentrations of NV-07al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…ssUV caused significant immunosuppression at doses as low as 1740 mJ per cm 2 72 h prior to antigen challenge. The average MED of subjects with the range of skin types that we tested was about 4000 mJ per cm 2 (Kuchel et al, 2002(Kuchel et al, , 2003Friedmann et al, 2004) and therefore immunosuppression occurred at ssUV doses lower than what was required to cause sunburn. We have also recently shown that a single exposure to 3420 mJ per cm 2 ssUV 24 or 48 h prior to elicitation of a DTH to tuberculin-purified protein resulted in a suppressed response (Friedmann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ssUV caused significant immunosuppression at doses as low as 1740 mJ per cm 2 72 h prior to antigen challenge. The average MED of subjects with the range of skin types that we tested was about 4000 mJ per cm 2 (Kuchel et al, 2002(Kuchel et al, , 2003Friedmann et al, 2004) and therefore immunosuppression occurred at ssUV doses lower than what was required to cause sunburn. We have also recently shown that a single exposure to 3420 mJ per cm 2 ssUV 24 or 48 h prior to elicitation of a DTH to tuberculin-purified protein resulted in a suppressed response (Friedmann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NV‐38, a synthetic analogue of dehydroequol (7‐hydroxy‐3′,4′‐dimethyoxy‐isoflav‐3‐ene; Novogen Ltd, North Ryde, NSW, Australia) and equol (4,7‐dihydroxyisoflavane; Sigma‐Aldrich, Castle Hill, New South Wales, Australia) were each dissolved as a 40 m m stock solution in DMSO (dimethyl sulfoxide), then diluted in a vehicle of propylene glycol–ethanol–water in a ratio of 1:2:1 as described previously 3 to provide lotions of 0, 5, 10, 20 and 40 μ m with 0.001% DMSO. The vehicle control base lotion contained 0.001% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…They may act as antioxidants, a property inherent from their polyphenolic molecular structure, and some of them also have binding affinity for oestrogen receptors and are therefore recognized as phytoestrogens. Topical application of some isoflavonoids is reported to have anti‐inflammatory efficacy in both the human and the mouse skin, 2 , 3 as well as inhibitory action against the activation of nuclear factor‐κB 4…”
mentioning
confidence: 99%
“…We have previously demonstrated comparable immunosuppression ($21%) with a similar single irradiation protocol [6], and higher immunosuppression ($40%) with multiple suberythemal exposures to ssUV [5].…”
mentioning
confidence: 82%
“…The Mantoux reaction is used clinically to assess previous exposure to Mycobacterium tuberculosis or the Bacille Calmette Guerin vaccine, and has been used previously in our laboratory as a model of UV immunosuppression in humans [5,6].…”
mentioning
confidence: 99%